Faculty Response to Deselection in Academic Libraries: A Psycholinguistic Analysis. Issue 2 (3rd April 2017) - Agee, Ann
ABSTRACT: Deselection is a necessary but politically sensitive part of an academic librarian's responsibilities. To provide an overview of the emotional dynamics involved in weeding an academic collection, this article analyzes editorials, articles, and book chapters chronicling faculty response to weeding from a psycholinguistic viewpoint. Using computer-based text analysis, these accounts are examined for the amount and type of emotional content they contain. These findings provide a template for what librarians can expect when beginning a deselection process and point to best practices for working effectively with faculty to create a robust and healthy collection.